Enhancing Student Learning Through Collaborative Inquiry: Determining the Refractive Index of Various Substances - Islom Ruziyev; Behruz Sayfullayev; Otabek Khushnazarov; Akmal Abdimuminov; Khadicha Mamatkulova (Scientia Publica Media, 2025)
The refractive index is a fundamental property of materials that describes how light propagates through a medium, enabling an understanding of optical phenomena such as refraction. This study investigates the refractive indices of water, oil, and glass using hands-on experimentation based on Snell’s Law. The researchers, who were also the participants, conducted the study as part of an independent project under the Cambridge AS Level Physics curriculum. Utilizing basic laboratory materials, including a ray box, protractor, and transparent containers, the experiment involved measuring the angles of incidence and refraction to calculate refractive indices. Each measurement was repeated three times for accuracy, and multiple angles of incidence were tested for consistency. The results showed a strong agreement between experimental and theoretical values, with refractive indices of 1.33 for water, 1.46 for oil, and 1.52 for glass, yielding percent errors of 0%, 0.68%, and 0.66%, respectively. These findings confirmed the reliability of the methodology and the validity of Snell’s Law. Minor deviations were attributed to potential sources of error, such as measurement inaccuracies and material impurities. This hands-on activity enhanced the researchers’ conceptual understanding of light behavior while promoting critical thinking, problem-solving, and independent research skills. The perspective of the students was meaningful as they enjoyed the activity. The collaborative nature of the activity was an outlet for the participants to enhance their learning. The practical approach fostered a deeper appreciation for experimental physics and demonstrated the importance of systematic data collection and analysis in scientific inquiry. By bridging theory with practice, the study highlighted the value of active learning in understanding complex physical concepts.